Pengaruh Sistem Pengendalian Intern, KompetensiSumber Daya Manusia Dan Pemanfaatan TeknologiInformasi Terhadap Kualitas Laporan KeuanganPemerintah Daerah (Studi Empiris Pada Dinas Pendapatan Pengelolaan Keuangan Dan Aset Daerah/DPPKAD Kabupaten Boyolali) - Sukmaningtyas, Shinta; , Drs. Suyatmin Waskito Adi, M.Si (2017)
The study aimed to determine the effect of internal control system, human resource competency and the utilization of information technology on the Quality of local Government Financial Report (LKPD) in DPPKAD of Boyolali regency. This research uses quantitative method with primary data that collecting questionnaire. Population of this research is employee department staff at DPPKAD Boyolali. The used sampling method is the saturated samples. Data collection is done by giving as many as 83 copies of the questionnaire, which was distributed to respondents on DPPKAD of Boyolali Regency. Sum samples are 61 respondent. Based on the analysis result, obtained that the internal control of system, the human resource competency and the utilization of information technology have significant effect on the Quality of local Government Financial Report (LKPD) in DPPKAD of Boyolali Regency.